Deletion of bone marrow-derived receptor for advanced glycation end products inhibits atherosclerotic plaque progression - Morris-Rosenfeld, Samuel; Blessing, Erwin; Preusch, Michael; Albrecht, Claudia; Bierhaus, Angelika; Andrassy, Martin; Nawroth, Peter Paul; Rosenfeld, Michael E.; Katus, Hugo; Bea, Florian (European journal of clinical investigation, 2011)
Eur J Clin Invest 2011; 41 (11): 1164-1171 Abstract Background The multiligand receptor for advanced glycation end products (RAGE) of the immunoglobulin superfamily is expressed on multiple cell types implicated in the inflammatory response in atherosclerosis. We sought to determine the role of bone marrow-derived RAGE in different stages of atherosclerotic development in apolipoprotein E-deficient mice (apoE−/−). Methods Seven- and 23-week-old apoE−/− mice (n = 40) were lethally irradiated and given bone marrow from RAGE null (RAGE−/−/apoE−/−) or RAGE-bearing (RAGE+/+/apoE−/−) mice to apoE−/− mice to generate double knockout bone marrow chimera (RAGE−/−/apoE−/−bmc and RAGE+/+/apoE−/−bmc-, respectively). After 16 weeks on a standard chow diet, mice were sacrificed and atherosclerotic lesion formation was evaluated. Results Plaques in the aortic root of the young mice showed no significant difference in maximum plaque size (217 470 ± 17 480 μm2 for the RAGE−/−/apoE−/−bmc mice compared to 244 764 ± 45 840 μm2), whereas lesions in the brachiocephalic arteries of the older RAGE−/−/apoE−/−bmc mice had significantly smaller lesions (94 049 ± 13 0844 μm2 vs. 145 570 ± 11 488 μm2, P < 0.05) as well as reduced average necrotic core area (48 600 ± 9220 μm2 compared to 89 502 ± 10 032 μm2, P < 0.05) when compared to RAGE+/+/apoE−/−bmc mice. Reduced plaque size and more stable plaque morphology was associated with significant reduced expression of VCAM-1, ICAM-1 and MCP-1. Accumulation of the RAGE ligand HMGB-1 was also significantly reduced within the lesions of RAGE−/−/apoE−/−bmc mice. Conclusions This study demonstrates that bone marrow-derived RAGE is an important factor in the progression of atherosclerotic plaques.
Gesehen am 08.09.2022